Asociación entre el test de caminata de seis minutos y factores de riesgo cardiovascular en portugueses obesos - Rômulo Araújo, F. [UNESP]; Cyrino, Edilson Serpeloni; Enio, R. Vaz R.; Renata Selva tici Borges, J.; Silva, Analiza Mónica; Minderico, Cláudia Sofía; Rocha, Paulo Manuel; Santa-Clara, Helena; Baista, Fátima; Sardinha, Luis Bettencourt (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2012)
Background: A better physical fitness may have survival advantages in adults. Aim: To analyze the relationship between cardiorespiratory fitness and cardiovascular risk factors among obese subjects aged 58 years and older. Material and Methods: Cardiorespiratory fitness using the six-minute walk test, body composition by dual-energy x-ray absorptiometry and blood pressure were measured in a non-representative sample of 76 obese Portuguese subjects aged 58 to 87 years (55 women). Participants were stratified in tertiles of walking capacity according to the six-minute walk test. Results: Six minutes walk test results were negatively correlated with percentage body fat (r = -0.28; p = 0.012) and systolic blood pressure (r = -0.23; p = 0.045). Participants located in the lowest tertile for the six minutes walk test had an odds ratio of 4.34 (95% confidence intervals: 1.02-18.43) for elevated blood pressure. Conclusions: A lower six minutes walk test result is associated with a higher risk for high blood pressure.
Cardiovascular fitness and cardiovascular risk factors among obese men and women aged 58 years and older, in Portugal
Keywords: Aged; Hypertension; Obesity; Physical fitness